How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline. (1st February 2023) - Zhu, Ge; Zhang, Haiyun; Yuan, Ru; Huang, Meng; Liu, Fei; Li, Mo; Zhang, Yongming; Rittmann, Bruce E.
Highlights: Addition of quinoline to nitrifying biomass led to inhibition of nitrification. Bioaugmenting Comamonas testosteroni or Rhodococcus ruber relieved the inhibition. Nitrification inhibition came from intermediate, 2HQ, instead of quinoline itself. Adding C. testosteroni or R. ruber enriched for nitrospira. Nitrospira appeared to be carrying out commamox metabolism. Abstract: Because many wastewater-treatment plants receive effluents containing inhibitory compounds from chemical or pharmaceutical facilities, the input of these inhibitors can lead to failure of nitrification and total-N removal. Nitrification de facto is the more important process, as it is the first step of nitrogen removal and involves slow-growing autotrophic bacteria. In this work, quinoline, the target compound severely inhibited nitrification: The biomass-normalized nitrification rate decreased four-fold in the presence of quinoline. The inhibition was relieved by bioaugmenting Comamonas testosteroni or Rhodococcus ruber to the nitrifying biomass. Because the inhibition was derived from a quinoline intermediate, 2‑hydroxyl quinoline (2HQ), not quinoline itself, nitrification was accelerated only after 2HQ disappeared due to the addition of R. ruber or C. testosteroni. R. ruber was superior to C. testosteroni for 2HQ biodegradation and accelerating nitrification. Besides accelerating nitrification, adding C. testosteroni or R. ruber led to the enrichment of Nitrospira, which appeared to be carrying out commamox metabolism, since ammonium-oxidizing bacteria were not enriched. Graphical abstract: Image, graphical abstract